Implementation of Minister of Transportation Regulation Number 27 of 2018 concerning Street Lighting Equipment in Karimun Regency - Yusmiyanti, Yusmiyanti; Meilani, Nur Laila; Adianto, Adianto (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Public services are efforts provided by a government agency to meet all community needs in the form of goods, services and administration carried out in accordance with its principles and responsibilities. Public street lighting (PJU) is a form of public service that the public has the right to enjoy as regulated in Minister of Transportation regulation number 27 of 2018 concerning Street Lighting Equipment. The Karimun Regency Government, through the duties and functions of the public housing and residential areas service (PERKIM), Karimun Regency, is the agency that organizes public street lighting (PJU). This research was conducted using Merille S Grindle's theory (2011) which was influenced by two large variables, namely the content of policy and the implementation environment, using descriptive research methods and a qualitative approach. The results of the research conducted by the author show that the implementation of the Minister of Transportation's regulation number 27 of 2018 concerning street lighting equipment in Karimun Regency has been carried out well, which can be seen from the results of interviews and observations made by researchers of the parties involved.